Comparison of daptomycin, vancomycin, and ampicillin-gentamicin for treatment of experimental endocarditis caused by penicillin-resistant enterococci. - Ramos, M C (1992)
Infections with enterococci that are resistant to multiple antibiotics are an emerging clinical problem. We evaluated the antibiotic treatment of experimental enterococcal endocarditis caused by two strains with different mechanisms of penicillin resistance. Enterococcus faecalis HH-22 is resistant to aminoglycosides and penicillin on the basis of plasmid-mediated modifying enzymes; Enterococcus raffinosus SF-195 is susceptible to aminoglycosides but is resistant to penicillin on the basis of low-affinity penicillin-binding proteins. Animals infected with strain HH-22 received 5 days of treatment with the following: no treatment; daptomycin (20 mg/kg of body weight twice daily [b.i.d.], intramuscularly [i.m.]), vancomycin (20 mg/kg b.i.d., intravenously), or ampicillin (100 mg/kg three times daily, i.m.) plus gentamicin (2.5 mg/kg b.i.d. i.m.). Although vancomycin was superior to ampicillin-gentamicin (P less than 0.01), daptomycin was significantly better than all other treatment regimens (P less than 0.01) in reducing intravegetation enterococcal densities, although no vegetations were rendered culture negative by this agent. Animals infected with strain SF-195 received 5 days of no therapy, ampicillin, ampicillin-gentamicin, vancomycin, or daptomycin (all at the dosage regimens described above). Daptomycin, vancomycin, and ampicillin-gentamicin each lowered intravegetation enterococcal densities significantly better than did ampicillin monotherapy or no treatment (P less than 0.01); moreover, these three treatment regimens rendered significantly more vegetations culture negative than did ampicillin monotherapy or no treatment (P less than 0.05). Serum daptomycin levels remained above the MICs and MBCs for both enterococcal strains throughout the 12-h dosing interval used in the study. Daptomycin and vancomycin were both active in vivo in these models of experimental enterococcal endocarditis caused by penicillin-resistant strains, irrespective of the mechanism of resistance. This activity correlated with the unique cell wall sites of action of these agents (binding to lipoteichoic acid and pentapeptide precursor, respectively) compared with the sites of action of beta-lactams (penicillin-binding proteins). Beta-Lactamase production by strain HH-22 precluded in vivo efficacy with ampicillin-gentamicin combinations. In contrast, this combination was active in vivo against strain SF-195, which exhibited intermediate-level penicillin resistance (MIC, 32 micrograms/ml), likely reflecting the ability of high-dose ampicillin to achieve enough binding to low-affinity penicillin-binding proteins to cause augmented aminoglycoside uptake.